SGLT2i treatment during AKI and its association with major adverse kidney events - Alcantar-Vallin, Luz; Zaragoza, Jose J.; Díaz-Villavicencio, Bladimir; Hernandez-Morales, Karla; Camacho-Guerrero, Jahir R.; Perez-Venegas, Miguel A.; Carmona-Morales, Edgar J.; Oseguera-Gonzalez, Alexa N.; Murguia-Soto, Cesar; Chávez-Alonso, Gael; Arredondo-Dubois, José M.; Orozco-Chan, Carlos E.; et al. (Frontiers in Pharmacology, 2024)
The association between the administration of sodium-glucose cotransporter 2 inhibitors (SGLT2i) during acute kidney injury (AKI) and the incidence of major adverse kidney events (MAKEs) is not known.: This retrospective cohort study included patients with AKI and compared outcomes for those who were treated with SGLT2i during hospitalization and those without SGLT2i treatment. The associations of SGLT2i use with MAKEs at 10 and 30-90 days, each individual MAKE component and the prespecified patient subgroups were analyzed.Results: From 2021 to 2023, 374 patients were included-316 without SGLT2i use and 58 with SGLT2i use. Patients who were treated with SGLT2i were older; had a greater prevalence of diabetes, hypertension, chronic heart failure and chronic kidney disease; required hemodialysis less often; and presented stage 3 AKI less frequently than those who were not treated with SGLT2i. Logistic regression analysis with nearest-neighbor matching revealed that SGLT2i use was not associated with the risk of MAKE10 ) or with ). For death, the stepwise approach demonstrated that SGLT2i use was associated with a reduced risk (OR 0.08; 0.01-0.64), and no effect was found for kidney replacement therapy (KRT). The subgroups of patients who experienced a reduction in the risk of MAKE in patients with AKI treated with SGLT2i were those older than 61 years, those with an eGFR >81, and those without a history of hypertension or DM (p ≤0.05 for all).The use of SGLT2i during AKI had no effect on short-or mediumterm MAKE, but some subgroups of patients may have experienced benefits from SGLT2i treatment.